Adult Congenital Heart Disease and Percutaneous Interventions : Analysis of Cases over five years in a Bangladeshi Center - Fatema, Nurun Nahar (Cardiovascular Journal, 2022)
Background: In recent year ‘s considerable progress has been made in the early diagnosis and treatment of congenital heart disease (CHD) and a significant number of children are expected to survive into adulthood after completion of treatment. This has created a scope of a substantial population of patients with adult congenital heart disease. In Bangladesh, milder or simple from of congenital heart diseases are prevalent among populations but palliated and treated cases of CHD are gradually increasing the load of work for adult congenital heart disease (ACHD) professionals. Many of these cases can be treated by transcatheter intervention with excellent outcome. Methods: This is a retrospective study conducted in a tertiary level cardiac hospitals of Bangladesh from January 2015 to December 2020. All cases aging 18 years and above were included who had undergone cardiac catheterization or percutaneous interventions. Data were collected from Echocardiography department, Catheterization Laboratory and indoor department. Follow up data were collected from echocardiography and outpatient department. Results: Total Two hundred Ninety-four cases were enrolled for cardiac catheterization. Two hundred eighteen cases had various types of intervention. Most of the cases were in 18-25 years age group. Among shunt lesions, 165 cases (56.12%) had atrial septal defect (ASD), 48(22.02%) had ventricular septal defect (VSD), 32 (14.67%) had patent ductus arteriosus (PDA), and 4(1.83%) had patent foramen ovale (PFO). Device closure was performed in 120(55.04%) cases of ASD, 13(5.96%) cases of VSD, 30 (13.76%) cases of PDA and in 4(1.83%) cases of PFO. Nineteen (8.72%) had valvuloplasty for pulmonary stenosis (PS), 2 (0.68%) had valvuloplasty for aortic stenosis (AS), 2(0.068%) had coarctoplasty for coarctation of the aorta (CoA), 4 (1.83%) had percutaneous pulmonary valve implantation (PPVI). Seventeen (7.79%) cases had double intervention of ASD device closure and pulmonary stenosis, 5 (2,29%) cases had ASD and PDA device closure and 2 (0.92%) cases had PDA device closure and balloon coarctoplasty. ASD device was embolized in 4 cases. There were no other complications. Conclusion: Outcome of intervention in ACHD was found safe and effective and no significant short or long-term complications were noticed. Cardiovasc j 2022; 14(2): 121-127